Effect of myo-inositol supplementation in mixed ovarian response IVF cohort: a systematic review and meta-analysis - Zhang, Jianeng; Zhang, Huanhuan; Zhou, Wenjing; Jiang, Meiyan; Lin, Xianhua (Frontiers in Endocrinology, 2025)
ObjectiveThere has been substantial research conducted recently on the effect of myo-inositol (MI) on human reproduction. However, it still remains ambiguous about the therapeutic efficacy of MI in infertile women undergoing in vitro fertilization embryo transfer (IVF-ET). This systematic review and meta-analysis was carried out to investigate the efficacy of MI on IVF outcomes.MethodsLiteratures were searched in the PubMed, Web of Science, Cochrane Library, ScienceDirect and Wanfang databases. The methodological quality was assessed using the Cochrane Risk of Bias tool. Data were pooled using a random- or fixed-effects model according to study heterogeneity. The results are expressed as odds ratio (OR) or mean difference (MD) with 95% confidence intervals (CIs). Heterogeneity was measured by the I2 statistic. The protocol was prospectively registered with PROSPERO (CRD42024582149).ResultsEleven eligible studies with 981 participants reported the IVF outcomes of the MI group versus the control group. The synthesis results showed that the metaphase II (MII) oocyte rate was higher in the MI group than in the control group (OR 1.55, 95% CI 1.04-2.31, P=0.03). For polycystic ovary syndrome (PCOS) women, as well as non-obese PCOS women, a statistically significant improvement in MII oocyte rate were assumed after taking MI (OR 1.97, 95% CI 1.20-3.25, P<0.01; OR 1.92, 95% CI 1.09-3.37, P=0.02) while there is no statistically significant advancement showed in the poor ovary responder (POR) women(OR 0.97, 95% CI 0.35-2.68, P=0.95). The fertilization rate was higher in the MI group than in the control group (OR 1.62, 95% CI 1.21-2.16, P<0.01), for PCOS, non-obese PCOS and POR women (OR 1.59, 95% CI 1.16-2.18, P<0.01; OR 1.87, 95% CI 1.52-2.31, P<0.01; OR 2.42, 95% CI 1.48-3.95, P<0.01).ConclusionsOur results suggest that MI supplementation improves the MII oocyte rate and the fertilization rate. More high-grade evidence from prospective randomized studies is warranted.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024582149.